Screen Personal Tool to Improve Students Understanding of The Concept Of Summing Round Numbers in SDN 1 Linggasari - Hendi Novianto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of the writer is the students' lack of understanding of the concept of adding make numbers.While the purpose of this study is to determine how much influence the use of number line props on student motivation. And to find out how much influence the number line props have on understanding of the teaching material.The method that I use is to use number line props on the concept of adding whole numbers. This research was conducted through a cycle assessment process consisting of four stages (planning, implementing, observing, and reflecting) in three cycles of learning improvement. From the results of the analysis, the conclusions obtained from this study are: 1) The use of number line props in the material of adding whole numbers can increase students' understanding by 71.79%, namely from the initial condition 28.21% to 100% in the third cycle. 2)The use of number line props on the sum of integers material can increase the seriousness of students by 74.36%, namely from the initial condition 25.64% to 100% in the third cycle. Conclusions from this study Is an effective use of number line props to improve understanding of integers.